Oxford studies in metaphysics. Volume 6 - Bennett, Karen; Zimmerman, Dean W. (Oxford : Oxford University Press, 2011)
'Oxford Studies in Metaphysics' is the forum for the best new work in this flourishing field. Much of the most interesting work in philosophy today is metaphysical in character: this series is a much-needed focus for it.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Metaphysics